Microplastic contamination in two resident species from the Mondego Estuary (Portugal) the common cockle (Cerastoderma Edule) and the european green crab (Carcinus Maenas) - Pessoa, Tiago André Camões (2021)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia